A solidariedade como um dos valores norteadores da formação do professor de ciências e de biologia - Gomes, Carlos (2008)
This study has as its purpose to investigate the solidarity value and how it has been a principle on the teachers graduation in the Biological Science Course in a superior institution. As a theorical support, I chosed Edgard Morin, Paulo Freire, Leonardo Boff e Ernst Mayr, and others trying to clarify the importance of putting into the teacher's formation practices the values thematics, specially the solidarity. Pointing value's education, not only as a discipline to improve the study curriculum but even and only as an achive work, daily, taking exemples in postures that spread everybody involved in education, in order to get the human being formation on an universal and solidary proposal. For this purpose, it was used as methodological documents: analysis, questionaires and interviews, from a qualitative approaching, looking for a dialogue between specific values and contends that coexist or must coexist, in a Biological Licencing and Graduating Formation Course, the solidary in focus